ANALISIS YUIRIDIS MATERI MUATAN NORMA YANG TERMUAT DALAM PERATURAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA PONTIANAK NOMOR 1 TAHUN 2014 TENTANG TATA TERTIB DEWAN PERWAKILAN RAKYAT DAERAH KOTA PONTIANAK - FERRY HAIRADI. SH, NIM: A2021141020, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis focuses on the analysis of the substance of the juridical norms contained in the regulations of the Regional Representatives Council Pontianak City No. 1 Year 2014 About Rules Legislative Council Pontianak. By using the method of normative legal research conclusion: 1). Pontianak City Council that Regulation No. 1 Year 2014 About Pontianak City Council Standing Orders are not in accordance with the establishment of laws and regulations. it can be seen from the juridical basis is not appropriate, especially concerning the procedure or the procedure of its formation, which in the discussion of harmonization and synchronization between chapters done improperly. With that, the Regulation DPRD Pontianak City No. 1 of 2014 did not follow the principle of